Radio emission from a decade old Type I superluminous supernova, PTF10hgi: comparison with FRB121102. Issue 3 (1st September 2020) - Mondal, Surajit; Bera, Apurba; Chandra, Poonam; Das, Barnali
ABSTRACT: We perform a comparative study between the only radio-detected Type I superluminous supernova (SLSN) PTF10hgi, and the most active repeating fast radio burst FRB121102. This study has its root in the hypothesized FRB-SLSN connection that states that magnetars born in SLSN can power FRBs. The wide-band spectrum (0.6–15 GHz) of PTF10hgi presented here, provides strong evidence for the magnetar wind nebular origin of the radio emission. The same spectrum also enables us to make robust estimates of the radius and the magnetic field of the radio-emitting region and demonstrates that the nebula is powered by the rotational energy of the magnetar. This spectrum is then compared with that of FRB121102 which we extend down to 400 MHz using archival data. The newly added measurements put very tight constraint on the emission models of the compact persistent source associated with FRB121102. We find that while both sources can be powered by the rotational energy of the underlying magnetar, the average energy injection rate is much higher in FRB121102. Hence, we hypothesize that, if PTF10hgi is indeed emitting fast radio bursts, those will be much weaker energetically than those from FRB121102.